Political accommodation of Salafism in Germany: a long-term view - Emmerich, Arndt (Religion in public, 2023)
By Arndt Emmerich [Cover image note: Pierre Vogel delivering a seminar on voting during the 2023 elections in Turkey. ©Arndt Emmerich] “Am I a kafir [nonbeliever], if I vote for [Turkey’s president…